2006
DOI: 10.1021/jp063125k
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and Isomerization of 1,2-Benzisoxazole:  Single-Pulse Shock-Tube Experiments, Quantum Chemical and Transition-State Theory Calculations

Abstract: Isomerization and decomposition of 1,2-benzisoxazole were studied behind reflected shock waves in a pressurized driver, single-pulse shock tube. It isomerizes to o-hydroxybenzonitrile, and no fragmentation is observed up to a temperature where the isomerization is almost complete (approximately 1040 K at 2 ms reaction time). The isomerization experiments in this investigation covered the temperature range 900-1040 K. The lack of fragmentation is in complete contrast to the thermal behavior of isoxazole, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…It was also found that IIA and the unidentified component in plasma showed the same exact mass (data not shown), suggesting that the interference component was derived from IIA , possibly by isomerization. All structure moieties are not likely to undergo isomerization except for the isoxazole ring whose ring‐opening isomerization has previously been documented in the literature 12. Additionally, all product ions of the interference component were consistent with the postulated ring‐opened metabolite (Scheme ).…”
Section: Resultssupporting
confidence: 60%
“…It was also found that IIA and the unidentified component in plasma showed the same exact mass (data not shown), suggesting that the interference component was derived from IIA , possibly by isomerization. All structure moieties are not likely to undergo isomerization except for the isoxazole ring whose ring‐opening isomerization has previously been documented in the literature 12. Additionally, all product ions of the interference component were consistent with the postulated ring‐opened metabolite (Scheme ).…”
Section: Resultssupporting
confidence: 60%
“…For instance, the base-catalyzed isomerization of 1,2-benzisoxazoles to 2-cyanophenols proceeds through N-O bond ring-opening reaction triggered by deprotonation of the carbon atom adjacent to the nitrogen. [1,[7][8][9][10][11][12][13][14][15] Scheme 1. [5,6] Thermal and photochemical transformations of 1,2-benzisoxazoles are also known to take place as a result of N-O bond cleavage (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Named as the Kemp elimination, this reaction can be promoted by biocatalysis and has been used as an important model to rational enzyme design. [7,10] Previously, combining experimental and theoretical investigations on the parent isoxazole, we established that open-shell singlet vinylnitrenes (1A′′-VN) are key reactive intermediates respective PES of the parent isoxazole. [1,[7][8][9][10][11][12][13][14][15] Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the effects like real gas and boundary layer effects, chemists have developed the chemical thermometry method [32][33][34][35] to get the accurate reflected shock temperatures. In kinetics, as the accuracy in measuring the temperature is very important, the chemical thermometric method was used in our investigations.…”
Section: Methodsmentioning
confidence: 99%